Rhetorical strategies used in Malay research article conclusions - Loi,, Chek Kim; Lau,, Yoke Lian; Soon,, Chow Thai; Nur Shafiekah Sapan; Siti Aishah Ramli; Henry Bating (Global Academic Excellence (M) Sdn Bhd, 2021)
This paper explains a combination of genre-based knowledge and evaluative stance in the context of academic arguments used in the conclusion sections of Malay research articles. For this purpose, it draws on an analysis of the features in Appraisal theory (Martin & Rose, 2003) together with a move analysis (Swales, 1990, 2004). The data comprises empirical research articles. The conformity with the standard IMRD (Introduction- Method- Results- Discussion) is taken as the first similar feature when selecting the set of empirical research articles from the selected journals. Among others, the findings observe that evaluative stances produce rhetorical effects in Malay conclusions. When taking a stance, both the evoked Attitudes and inscribed Attitudes are employed. A closer examination shows that the evoked Attitudes and inscribed Attitudes are either used separately or simultaneously to realize a move.